2020
DOI: 10.1542/neo.21-3-e165
|View full text |Cite
|
Sign up to set email alerts
|

Milrinone Use in Persistent Pulmonary Hypertension of the Newborn

Abstract: Failure of the normal transition from in utero to ex utero physiology leads to “persistent” pulmonary hypertension of the newborn (PPHN). PPHN is frequently associated with low systemic blood pressure and low cardiac output because of increased right ventricular afterload and myocardial dysfunction. The general management of newborns with PPHN is geared toward maintenance of normothermia, normal serum electrolytes, normal intravascular volume, correction of acidosis, adequate sedation/analgesia, adequate venti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Therapeutic effects of injectable milrinone as an adjuvant to other therapies (including iNO) have been reviewed and validated in previous studies. In a review article, Qasim et al (4) .reviewed six studies on the effect of injectable milrinone in the management of PPHN, in which all reported a positive effect of injectable milrinone in the treatment of PPHN. The dose of milrinone in three of the studies was 50 µg / kg bolus and then 0.33 µg / kg/min infusion, while in three studies without bolus and with an infusion rate of 0.99 − 0.33 µg / kg.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therapeutic effects of injectable milrinone as an adjuvant to other therapies (including iNO) have been reviewed and validated in previous studies. In a review article, Qasim et al (4) .reviewed six studies on the effect of injectable milrinone in the management of PPHN, in which all reported a positive effect of injectable milrinone in the treatment of PPHN. The dose of milrinone in three of the studies was 50 µg / kg bolus and then 0.33 µg / kg/min infusion, while in three studies without bolus and with an infusion rate of 0.99 − 0.33 µg / kg.…”
Section: Discussionmentioning
confidence: 99%
“…PPHN is usually associated with systemic hypotension and decreased cardiac output due to increased right ventricular afterload and myocardial insu ciency (2,3) . Management of neonates with PPHN includes maintenance therapy to maintain normal body temperature, serum electrolytes, intravascular volume, acid-base balance, analgesia, ventilation, and oxygenation (4) . Timely administration of inotropic and vasoactive drugs can increase cardiac output, maintain adequate blood pressure, and improve oxygen delivery (4) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Milrinone is a kind of bipyridine with vasodilator properties, which is generally used in the therapies for cardiopulmonary diseases. 16 , 17 For instance, Qasim and Jain revealed that milrinone can ameliorate persistent pulmonary hypertension in newborn through the great improvement for cardiac function and the reduction for pulmonary vascular resistance. 16 Tang et al performed a meta-analysis for the function of milrinone on patients with acute heart failure (AHF) or acute myocardial infarction (AMI); they uncovered that milrinone may be an effectively clinical drug for the treatment of AHF and AMI.…”
Section: Introductionmentioning
confidence: 99%
“… 16 , 17 For instance, Qasim and Jain revealed that milrinone can ameliorate persistent pulmonary hypertension in newborn through the great improvement for cardiac function and the reduction for pulmonary vascular resistance. 16 Tang et al performed a meta-analysis for the function of milrinone on patients with acute heart failure (AHF) or acute myocardial infarction (AMI); they uncovered that milrinone may be an effectively clinical drug for the treatment of AHF and AMI. 17 More importantly, growing evidences uncovered the clinical use of milrinone in neurological and neurocritical care patients, including subarachnoid hemorrhage (SAH) and stroke.…”
Section: Introductionmentioning
confidence: 99%